Endoplasmic reticulum membrane localization of Rce1p and Ste24p, yeast proteases involved in carboxyl-terminal CAAX protein processing and amino-terminal a-factor cleavage - Schmidt, Walter K. (The National Academy of Sciences, 1998)
Proteins terminating in the CAAX motif, for example Ras and the yeast a-factor mating pheromone, are prenylated, trimmed of their last three amino acids, and carboxyl-methylated. The enzymes that mediate these activities, collectively referred to as CAAX processing components, have been identified genetically in Saccharomyces cerevisiae. Whereas the Ram1p/Ram2p prenyltransferase is a cytosolic soluble enzyme, sequence analysis predicts that the other CAAX processing components, the Rce1p and Ste24p proteases and the Ste14p methyltransferase, contain multiple membrane spans. To determine the intracellular site(s) at which CAAX processing occurs, we have examined the localization of the CAAX proteases Rce1p and Ste24p by subcellular fractionation and indirect immunofluorescence. We find that both of these proteases are associated with the endoplasmic reticulum (ER) membrane. In addition to having a role in CAAX processing, the Ste24p protease catalyzes the first of two cleavage steps that remove the amino-terminal extension from the a-factor precursor, suggesting that the first amino-terminal processing step of a-factor maturation also occurs at the ER membrane. The ER localization of Ste24p is consistent with the presence of a carboxyl-terminal dilysine ER retrieval motif, although we find that mutation of this motif does not result in mislocalization of Ste24p. Because the ER is not the ultimate destination for a-factor or most CAAX proteins, our results imply that a mechanism must exist for the intracellular routing of CAAX proteins from the ER membrane to other cellular sites.